Identification of Students' Creative Thinking Ability in Solving Open-Ended Problems on Rigid Object Equilibrium Material Using Digital-Based Assessment - Ratna Purnamawati; Wasis Wasis; Muhammad Satriawan (Universitas Negeri Surabaya, 2026)
Objective: To identify students' creative thinking ability in solving open-ended problems on rigid object equilibrium material through digital-based assessment at SMA Negeri 1 Badegan. Method: A descriptive quantitative method involving 108 eleventh-grade students at SMA Negeri 1 Badegan. Data were collected through observation, documentation, and open-ended problem tests administered digitally using Google Form integrated with a learning management system (LMS). Students' creative thinking ability was analyzed based on four indicators: fluency, flexibility, originality, and elaboration. The data analysis was conducted by calculating the percentage of achievement for each indicator and categorizing students' creative thinking ability levels. Results: The results showed that students' creative thinking ability in solving open-ended problems on rigid object equilibrium material was still relatively low. The fluency indicator obtained an average achievement score of 42.98% (poor category), flexibility reached 30.53% (very poor category), originality obtained 20.35% (very poor category), and elaboration reached 25.61% (very poor category). The findings indicate that students experienced difficulties in generating diverse ideas, producing original solutions, and providing detailed explanations when solving open-ended physics problems. The utilization of digital platforms through Google Form and LMS facilitated systematic data collection, efficient response management, and documentation of students' creative thinking performance. Novelty: The novelty of this study lies in the identification of students' creative thinking ability in rigid object equilibrium material through digital-based assessment. The integration of digital platforms as a data collection medium provides an efficient approach for analyzing students' responses to open-ended physics problems and contributes to the development of technology-supported physics assessment practices.